Efecto de los tratamientos en el control de las poblaciones del "acaro de las yemas" (Aceria sheldoni EWING) del limonero - Lacasa, A.=700 1 Martinez, M.C.; Torres, J.
(En, Es)
ilus., 18 ref.
Keywords: ACERCA SHELDONI; ACARINA; CITRUS; CONTROL QUIMICO; ESPAÑA; LIMONERO